Parental Sexual Education Practices in the Tolotang Indigenous Community of South Sulawesi, Indonesia (JED (Jurnal Etika Demokrasi), 2026)
The urgency of this research departs from the persistence of culturally rooted taboos that hinder open and accurate sexual education within the Tolotang indigenous community, leaving children and adolescents with limited guidance on puberty, bodily integrity, and protection from sexual violence. This study aims to: (1) explore how parents in the Tolotang community interpret sexual education; (2) describe the forms of sexual education practiced within Tolotang families; and (3) identify the barriers encountered in implementing sexual education. The research employed a qualitative approach with in-depth interviews, participatory observation, and documentation involving 10 purposively selected informants—Tolotang parents with children aged 5–22 years and Tolotang youth aged 17–22 years. Data were analyzed through iterative stages of data condensation, data display, and conclusion drawing and verification. The findings show that parents primarily construct sexual education as moral, ethical, and polite conduct in society, closely linked to the cultivation of shame (siri’), family honor, and strict adherence to customary norms, while sexuality itself is perceived as a highly sensitive and taboo topic for open discussion with children. Sexual education is conveyed implicitly through advice and prohibitions regarding interaction with the opposite sex, behavioral monitoring and control, and parental role modelling. Key obstacles include limited parental knowledge, the absence of culturally grounded institutional guidelines or programs, and strong beliefs that sexual issues should not be discussed explicitly. The novelty of this research lies in its contextualized analysis of sexual education within a specific indigenous belief community. The study contributes conceptually and practically to the development of culturally responsive sexual education models in minority cultural settings.
Keywords: Sexual Education; Indigenous Community; Parental Practices; Tolotang Indigenous Community; South Sulawesi Indonesia